Determination of acid dissociation constants of triazole fungicides by pressure assisted capillary electrophoresis - Konášová, Renáta; Dytrtová, Jana Jaklová; Kašička, Václav (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
Pressure assisted capillary electrophoresis was applied to determination of acid dissociation constants (pKa) of six widely used triazole fungicides (cyproconazole, epoxiconazole, flusilazole, tebuconazole, penconazole and propiconazole) in aqueous medium. The pKa values were determined from the dependence of effective electrophoretic mobility of the triazole fungicides on p[H(+)] of the background electrolyte (BGE) using non-linear regression analysis. The p[H(+)] was used instead of pH to reflect the increased ionic strength of the strongly acidic BGEs (pH<1.75) as compared to the BGEs at pH equal to or greater than 1.75. Prior to the pKa calculation, the measured effective electrophoretic mobilities were corrected to the reference temperature (25°C) and constant ionic strength (25mM). The regression function was modified to allow the determination of pKa in the BGEs of varying ionic strength. The electrophoretic measurements showed that the above triazole fungicides are very weak bases - their pKa values were found to be in the range 1.05-1.97 and were in a good agreement with the values calculated by SPARC online pKa calculator.
Keywords: Fungicides, Industrial; triazoly; Epoxy Compounds; Electrolytes; elektrolyty; tlak; Triazoles; osmolární koncentrace; průmyslové fungicidy; silany; Electrophoresis, Capillary; Osmolar Concentration; Silanes; koncentrace vodíkových iontů; epoxidové sloučeniny; Hydrogen-Ion Concentration; elektroforéza kapilární; Pressure